Phonetic interference in the vowel production of Yemeni Arabic-English bilinguals - Sumaya Faisal Alshamiri,; Shahidi, A.H.; Abunima, Somaya (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study observes whether Yemeni Arabic-English bilinguals demonstrate any phonetic interference in their vowel production by examining the acoustic similarities and differences of both of their languages. Besides, it compares Yemeni Arabic vowels of bilinguals to monolingual production to identify any L2 influence on L1. Sixty subjects speaking native Yemeni Arabic were involved. Thirty were bilinguals who had acquired English as an L2, and the remaining 30 were monolinguals. All subjects produced a list of Arabic words with the target vowels /iː, aː, uː/ in the word-medial position. Moreover, the bilingual subjects also produced a list of English words with the target vowels /iː, ɑː, uː/ in the word-medial position. Vowel Duration, First Formant (F1), Second Formant (F2), and Third Formant (F3) of the target vowels were acoustically analysed. Findings revealed that in the F2 of /aː/, Yemeni Arabic-English bilinguals demonstrate L2 influence on L1 in the form of L1 phonetic drift towards their L2. On the contrary, findings show no significant influence of L2 English on L1 Yemeni Arabic long vowels /iː/ and /uː/. However, findings reveal a slight drift in L1 Yemeni Arabic vowels towards L2 Yemeni English vowels, causing closer acoustic vowel space between both languages, suggesting an assimilatory process. Furthermore, Yemeni Arabic-English bilinguals formed new categories for their L2 Yemeni English vowels for the acoustic properties: vowel duration and F1 of /iː/, F2 of /ɑː/, as well as F1 and F2 of /uː/ whereas they developed merged categories for the remaining acoustic properties.